The Leptogium juressianum complex in southeastern Brazil - Kitaura, Marcos J. [UNESP]; Marcelli, Marcelo (Mycotaxon Ltd, 2012)
Leptogium subjuressianum and L. subjuressianum var. caparoense are new Brazilian taxa growing mostly in the southeastern mountains. They are differentiated from European taxa by the ornamentation of the upper surface.
Keywords: lobules; margin; granular isidia